An NIR-Triggered Au Nanocage Used for Photo-Thermo Therapy of Chronic Wound in Diabetic Rats Through Bacterial Membrane Destruction and Skin Cell Mitochondrial Protection - Ding, Jiaxin; Gao, Binbin; Chen, Zhenhua; Mei, Xifan (Frontiers in Pharmacology, 2021)
Bacterial infection and its severe oxidative stress reaction will cause damage to skin cell mitochondria, resulting in long-lasting wound healing and great pain to patients. Thus, delayed wound healing in diabetic patients with staphylococcus aureus infection is a principal challenge worldwide. Therefore, novel biomaterials with multifunction of bacterial membrane destruction and skin cell mitochondrial protection are urgent need to develop to address this challenge. In this work, novel gold cage (AuNCs) modified with epigallocatechin gallate (EGCG) were prepared for the treatment of delayed diabetic wounds. The results showed that Au-EGCG had a high and stable photothermal conversion efficiency under near infrared irradiation, and the scavenging rate of Au-EGCG to Staphylococcus aureus could reach 95%. The production of large amounts of ROS leads to the disruption of bacterial membranes, which induces bacterial lysis and apoptosis. Meanwhile, Au-EGCG@H promoted the migration and proliferation of human umbilical cord endothelial cells, reduced cellular mitochondrial damage and oxidative stress in the presence of infection, and significantly increased the expression of basic fibroblast growth factor and vascular endothelial growth factor. In addition, animal studies showed that wound closure was 97.2% after 12 days of treatment, and the healing of chronic diabetic wounds was significantly accelerated. Au-EGCG nano platforms were successfully prepared for promoting cell migration and angiogenesis in diabetic rats while removing staphylococcus aureus, reducing oxidative stress in cells as well as restoring impaired mitochondrial function. Au-EGCG provides an effective, biocompatible and multi-functional therapeutic strategy for chronic diabetic wounds.